2009
DOI: 10.1073/pnas.0902420106
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger directed double-strand breaks within CAG repeat tracts promote repeat instability in human cells

Abstract: Expanded triplet repeats have been identified as the genetic basis for a growing number of neurological and skeletal disorders. To examine the contribution of double-strand break repair to CAG⅐CTG repeat instability in mammalian systems, we developed zinc finger nucleases (ZFNs) that recognize and cleave CAG repeat sequences. Engineered ZFNs use a tandem array of zinc fingers, fused to the FokI DNA cleavage domain, to direct double-strand breaks (DSBs) in a site-specific manner. We first determined that the ZF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 51 publications
3
64
0
Order By: Relevance
“…In the absence of NER, other repair processes that enhance repeat instability may become involved in resolving the bubble. For example, nicks in the two strands of the bubble would generate a double-strand break, whose repair we have previously shown is accompanied by a substantial increase in CAG repeat contractions (48). The persistence of this or some other abnormal structure is consistent with the idea that convergent transcription stresses the cell in a way that can lead to cell death.…”
Section: Discussionsupporting
confidence: 62%
“…In the absence of NER, other repair processes that enhance repeat instability may become involved in resolving the bubble. For example, nicks in the two strands of the bubble would generate a double-strand break, whose repair we have previously shown is accompanied by a substantial increase in CAG repeat contractions (48). The persistence of this or some other abnormal structure is consistent with the idea that convergent transcription stresses the cell in a way that can lead to cell death.…”
Section: Discussionsupporting
confidence: 62%
“…Because zinc fingers can be readily reengineered to bind different DNA sequences (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including CAG repeats (30), they could, in principle, be used to target the HTT gene at a transcriptional level. Furthermore, zinc fingers can be easily concatenated into long chains, and different linker designs can alter the interaction kinetics substantially (31).…”
mentioning
confidence: 99%
“…To test for a possible connection between Hsp90 function and the stability of repeat tracts, we employed a selection assay in human FLAH25 cells, which we have previously used to identify modifiers of CAG repeat stability (Gorbunova et al 2003(Gorbunova et al , 2004Lin et al 2006Lin et al , 2010Lin and Wilson 2007;Mittelman et al 2009). FLAH25 cells carry an integrated HPRT minigene that contains a single intron interrupted by 95 copies of a CAG repeat (Fig.…”
Section: Drug and Genetic Inhibition Of Hsp90mentioning
confidence: 99%
“…In both yeast and mammalian cells, CAG repeat tracts have been shown to be naturally prone to DSBs (Jankowski et al 2000;Meservy et al 2003). We previously developed CAG-specific zincfinger nucleases that introduce DSBs within CAG repeats and showed that they destabilize CAG repeats in a lengthdependent manner in human and rodent cells, triggering a substantial induction of large repeat contractions (Mittelman et al 2009). The susceptibility of CAG repeats to DSBs and the ability of Hsp90 inhibition to interfere with DSB repair led us to evaluate the possible role of Hsp90 in nucleotide repeat instability.…”
Section: Introductionmentioning
confidence: 99%